LRAD – The Radiometer for the Lunar South Pole Hopper μNOVA. - Hamm, Maximilian; Grott, Matthias; Knollenberg, Jörg; Robinson, Mark S.; Atwell, M.; Mabe, K.; Martin, T.; Rauer, Heike (2023)
Permanently shadowed regions (PSRs) are present at the Lunar poles. The surface temperature inside a PSR can remain below 110K, low enough fow stable water ice to exist in vacuum. The presence of ater ice at the Lunar Poles has been indicated by remote sensing bservations, in particular by the Lunar Prospector, LCROSS, and LRO missions. As part of the NASA Commerical Lunar Payload Service program, the Nova-C lander will be build and operated by the US-based company Intuitive Machines. Nova-C will land near the Lunar south pole for in-situ inverstigations of potential volatiles in the regolith. Nova-C will carry the S.P. Hopper to the Moon which will in a sequence of short flights land within a PSR inside Marston crater (informal name) close to a potential landing site for the Artemis Astronauts [7]. The Hopper will map the lunar surface with two cameras and a themal infrared radiometer (LRAD).